Evaluación de la remoción de arsénico del sistema de islas flotantes artificiales (ifav) con la especie pasto vetiver (chrysopogon zizanioides) en agua corriente del sistema central de riego Toacaso periodo 2021-2022. - Aimacaña Gualpa, Esteban Eduardo (2022)
The main objective of this research was to evaluate the removal of arsenic (As) in tap water from the Toacaso Central Irrigation System, located in the "El Pueblo" neighborhood in the central area of the parish of Toacaso, through the use of the artificial floating islands system (IFAV) with species of pasto Vetiver (Chrysopogon zizanioides); an ecotechnological procedure that helped the increasing decontamination suffered by several bodies of water, which simultaneously unites efficiency, effectiveness and economy. The study was carried out in two phases; the phase one: through laboratory and in situ analysis with kits to measure arsenic. For the laboratory analyses, 3 water monitoring was carried out at 3 different points of the reservoir (inlet, center and outlet), during 3 months; then, in situ, with the use of kits 18 water samplings were carried out at the same points of the reservoir, every eight days. The results obtained through laboratory analysis show an As removal of 17% and 35% for the in situ phase. In phase two, the presence of arsenic in the morphology of the vetiver plant (root, stem and shoots) was evaluated using 24 random plant composite samples. The maximum amount absorbed by the root was 87.83 mg/kg, in the stem it was 9.35 mg/kg and in the shoots it was 11.7 mg/kg. 7 mg/kg and the values obtained in FT (translocation factor) was 0.27 mg/kg and in BCF (bio-concentration factor) a value of 190.62 mg/kg was obtained, demonstrating that the plant is an accumulator; however, it does not efficiently translocate arsenic in its morphology, so what it does is to phytostabilize the contaminant in its tissues. Finally, it was possible to prove that the IFAV system is a viable alternative for arsenic removal in the central reservoir of Toacaso, and that the roots have the greatest As retention capacity in the plant.